Safety of COVID-19 vaccines in patients with non-communicable diseases: a protocol for systematic review and meta-analysis of randomised controlled trials - Chengqian Shi; Mizhi Wu; Xinchang Wang; Kepeng Yang (BMJ Open)
Introduction The COVID-19 global pandemic has posed enormous threats to public health around the world. Vaccines are considered the best therapeutic strategy against the COVID-19 pandemic. However, the adverse reactions of vaccines significantly affect the rates of vaccination and may be more serious in patients with non-communicable diseases (NCDs). This protocol aims to conduct a systematic review and meta-analysis of randomised controlled trials (RCTs) which analysed the safety of vaccines in patients with NCDs.Methods and analysis This study will be according to the guidelines of the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols. A comprehensive search will be carried out to identify registered RCTs in PubMed, Embase, Web of Science, ClinicalTrials.gov and Cochrane Library between 1 January 2020 and 31 May 2022. Selection of trials, data extraction, risk of bias assessment and quality of evidence assessment will be done by two researchers, and disagreements will be resolved by the corresponding author. The primary outcomes are local and systemic adverse events of vaccines in patients with NCDs. Additional outcomes are related events caused by vaccine adverse events, including but not limited to cases of adverse events leading to discontinuation from a dose or withdrawal from participation in the trial. Heterogeneity will be assessed with I2 statistics and data analysis will be conducted with RevMan V.5.4.1.Ethics and dissemination This is a protocol and ethical approval is not necessary. The results of this protocol will be disseminated to peer-reviewed publications or conference presentations.PROSPERO registration number CRD42021254914.